Implementasi Manajemen Peserta Didik dalam Meningkatkan Prestasi Belajar Peserta Didik di SMA Negeri 3 Panyabungan (International Forum of Researchers and Lecturers, 2025)
Implementation of Student Management in Improving Student Learning Achievement at SMA Negeri 3 Panyabungan. In school management, the system must be improved, starting from student management, the recruitment process for educators and education staff must meet school requirements and then implement more creative learning to support increasing teacher competency. On the basis of the explanation above, the research intends to examine in more depth the implementation of students in improving students' learning achievement. The problem formulation is: 1) How is the management of students at SMA Negeri 3 Panyabungan, 2) What is the achievement of students at SMA Negeri 3 Panyabungan, 3) How is the implementation of student management in improving the learning achievement of students at SMA Negeri 3 Panyabungan. This research aims to determine student management which includes student achievement and the implementation of student management at SMA Negeri 3 Panyabungan. This research uses a qualitative descriptive approach which aims to fully describe the phenomena that occur in the field. The informants in this research were the school principal, student affairs, homeroom teacher and students. From the research results, student management at SMA Negeri 3 Panyabungan is very good, seen from the results of the students' achievements, both academic and non-academic achievements. Student management has a very important role in schools. The implementation of student management at SMA Negeri 3 Panyabungan is carried out well, giving full rights to students to develop the potential of each student. The conclusion of this research is that the implementation of student management at SMA Negeri 3 Panyabungan is good. This can be seen from the students' achievements both academically and non-academicly. Other achievements were also obtained from teachers and other staff in improving achievements at SMA Negeri 3 Panyabungan.